ADMINISTERING SOCIAL SECURITY: CHALLENGES YESTERDAY AND TODAY. - Puckett, Carolyn (Social Security Bulletin, 2010)
In 2010, the Social Security Administration (SSA) celebrates the 75th anniversary of the passage of the Social Security Act. In those 75 years, SSA has been responsible for programs providing unemployment insurance, child welfare, and supervision of credit unions, among other duties. This article focuses on the administration of the Old-Age, Survivors, and Disability Insurance program, although it also covers some of the other major programs SSA has been tasked with administering over the years--in particular, Medicare, Black Lung benefits, and Supplemental Security Income. The article depicts some of the challenges that have accompanied administering these programs and the steps that SSA has taken to meet those challenges. Whether implementing complex legislation in short timeframes or coping with natural disasters, SSA has found innovative ways to overcome problems and has evolved to meet society's changing needs.